Reactivation of Maculopapular Drug Eruption Lesions Suspected to be Caused by Allopurinol During 72 Hours-Patch Test: a Case Report - Triasari Oktavriana; Irene Ardiani Pramudya Wardhani (Syntax Literate, 2022)
Maculopapular drug eruption is a delayed-type T-cell-mediated hypersensitivity reaction to a drug that is most commonly encountered within one week of suspected drug exposure. Allopurinol is a drug that is often found as a cause of drug allergic eruptions. The drug patch test can be used to identify the causative agent of a drug eruption. A 56-year-old man came with the chief complaint of itchy red patches on his face, chest, back, hands and feet for the past two weeks. The patches appeared five days after the patient took allopurinol for his hyperuricemia. The patient was diagnosed with maculopapular drug eruption with suspected to be caused by allopurinol. Six weeks after the patient was free from any lesions and eligible, a patch test was performed but the results were negative in all chambers on all reading days. At 72 hours after the patch test, there was reactivation of the skin lesions which obscured the patch test results. Maculopapular drug eruptions can be triggered by drug metabolites or drug absorption from the patch test itself is sufficient to cause reactivation.